2010
DOI: 10.1029/2008je003208
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory simulations of Mars evaporite geochemistry

Abstract: [1] Evaporite-rich sedimentary deposits on Mars were formed under chemical conditions quite different from those on the Earth. Their unique chemistries record the chemical and aqueous conditions under which they were formed and possibly subsequent conditions to which they were subjected. We have produced evaporite salt mineral suites in the laboratory under two simulated Martian atmospheres: (1) present-day and (2) a model of an ancient Martian atmosphere rich in volcanic gases. The composition of these synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…As the CRISM global mapping data set nears completion, broader searches for evaporites in paleolakes will be possible. Exploring the range of evaporites in Martian paleolakes could reveal not only how lake chemistry varied in space and time, but it may also constrain the composition of the ancient Martian atmosphere [e.g., Moore et al , 2010; Wray et al , 2009c].…”
Section: Discussionmentioning
confidence: 99%
“…As the CRISM global mapping data set nears completion, broader searches for evaporites in paleolakes will be possible. Exploring the range of evaporites in Martian paleolakes could reveal not only how lake chemistry varied in space and time, but it may also constrain the composition of the ancient Martian atmosphere [e.g., Moore et al , 2010; Wray et al , 2009c].…”
Section: Discussionmentioning
confidence: 99%
“…Although moganite has not yet been identified on Mars, its formation is dependent upon the presence of iron in the fluid as well as high activity of alkalis and/or sulfates (Heaney and Post 1992;Heaney 1995;McLaren and Pitkethly 1982). In addition Al 3+ can act as a catalyst in the formation of agate incorporating moganite (Story et al 2010;Moore et al 2010;Wang and Merino 1990). In situ and orbital observations have provided widespread evidence for the presence of iron-rich fluids in diagenetic and hydrothermal environments (Ming et al 2008) through detections of Fe-bearing sulfates (Squyres et al 2004;Wray et al 2011) and phyllosilicates (Poulet et al 2005;Bibring et al 2006); Al-phyllosilicates are less common but still present (Noe Dobrea et al 2010).…”
Section: Moganitementioning
confidence: 98%
“…Martian salts, however, were presumably formed under different chemical conditions compared to the Earth, with aqueous alteration possibly related to high temperature and, as a consequence, differences in the ionic balance. For explaining the origin of mobile ions in the Martian regolith, Moore et al ( 2010 ) suggested that the following possible explanations should be considered: alteration of basalts by hot hydrothermal fl uids, precipitation of volcanic-derived aerosol/gas compounds, groundwater/ igneous rock interactions, and, lastly, the falling of meteorites. Experiments on evaporite salts in simulated modern and ancient Martian conditions (e.g., Bullock On Earth, as well as on Mars, hydrous Mg sulfates abound in marine and continental evaporite environments.…”
Section: Earth Versus Mars Evaporite Environments: Limits To Detectinmentioning
confidence: 99%